Malaria in irrigated agriculture: papers and abstracts for the SIMA Special Seminar at the ICID 18th International Congress on Irrigation and Drainage, Montreal, 23 July 2002 - Boelee, Eline; Konradsen, Flemming; Hoek, Wim van der (International Water Management Institute, 2002)
The Special SIMA Seminar on Malaria in Irrigated Agriculture at the 18th ICID International Congress on Irrigation and Drainage was one of the activities aimed at increasing awareness in the agricultural community on the potential of environmental interventions to reduce malaria under Output 4 of SIMA. This document contains papers and abstracts submitted for this seminar in Montreal, Canada. The authors themselves are responsible for their contributions and it is hoped that the publication of these proceedings will stimulate discussions among participants of the seminar as well as in the wider SIMA Network. This seminar is organized by SIMA, the CGIAR Systemwide Initiative on Malaria and Agriculture, in collaboration with the International Water Management Institute (IWMI). This and subsequent scientific seminars will gather experts on malaria and agriculture to contribute to the development of a comprehensive knowledge base on malaria and agriculture.